Structure of Arabidopsis CESA3 catalytic domain with its substrate UDP-glucose provides insight into the mechanism of cellulose synthesis - Qiao, Zhu (2021)
Cellulose is synthesized by cellulose synthases (CESAs) from the glycosyltransferase GT-2 family. In plants, the CESAs form a six-lobed rosette-shaped CESA complex (CSC). Here we report crystal structures of the catalytic domain of Arabidopsis thaliana CESA3 (AtCESA3CatD) in both apo and uridine diphosphate (UDP)-glucose (UDP-Glc)–bound forms. AtCESA3CatD has an overall GT-A fold core domain sandwiched between a plant-conserved region (P-CR) and a class-specific region (C-SR). By superimposing the structure of AtCESA3CatD onto the bacterial cellulose synthase BcsA, we found that the coordination of the UDP-Glc differs, indicating different substrate coordination during cellulose synthesis in plants and bacteria. Moreover, structural analyses revealed that AtCESA3CatD can form a homodimer mainly via interactions between specific beta strands. We confirmed the importance of specific amino acids on these strands for homodimerization through yeast and in planta assays using point-mutated full-length AtCESA3. Our work provides molecular insights into how the substrate UDP-Glc is coordinated in the CESAs and how the CESAs might dimerize to eventually assemble into CSCs in plants.